Influence of Transformational Leadership on Performance: Does Organizational Culture Matter? Evidence from Deposit Taking Saccos in Kenya - Njoki, Catherine; K’Obonyo, Peter; Muindi, Florence; Rucha, Kingsford (European Journal of Business and Strategic Management, 2024)
Purpose: The general purpose of this study is to establish the influence of Transformational Leadership on Performance of Deposit Taking SACCOs in Nairobi city County, Kenya and more specifically establish the role of Organizational Culture on the relationship between transformational leadership and performance of the SACCOs. Methodology: The research philosophy embraced by this study was positivism. The research design used was descriptive research design with Census Survey employed on the forty (40) deposit taking Savings and Credit Cooperative Societies (SACCOs) in Nairobi City County, Kenya (SASRA, 2019). The study relied on primary data that was collected using close-ended structured questionnaires. Findings: The results obtained from this study reveal that transformational leadership has a significant influence on performance of DTSACCOs which is in line with transformational leadership theory that transformational leaders are able to articulate organizational goals and objectives in a bid to achieve the set objectives in organizations. At the same note, Organizational Culture was found to have a significant moderating role on the relationship between transformational leadership and organizational performance. The limitations of this study is that data was collected from at a snap short (one point in time) and hence limiting comparison. Unique Contribution to Theory, Practice and Policy: The study recommends that policy makers grow the overall sustainability, competitiveness, attractiveness and performance of the deposit taking SACCOs industry by developing legislative framework that strengthens the culture of SACCOs for efficient and effectiveness in their performance. Further it recommends that SACCO leaders cultivate suitable cultures that promote attainment of organizational goals.